The Application of Waterfall Model in Web-Based Social Assistance Application Development: Web-Based Social Assistance Application Development - ratna sari; Zulkifli Zulkifli (SYNTAX Jurnal Informatika, 2022)
Poverty in Indonesia is a very important problem at this time, so that it becomes a focus of attention for the government and becomes a development issue in Indonesia. The main strategy for reducing poverty in Indonesia is one of the many steps taken to suppress growth and eliminate poverty. Various efforts and policies have been made by the government to overcome this problem, one of which is by providing social assistance to people who have a weak economy. The social assistance includes the Hopeful Family Program, Non-Cash Food Assistance, Joint Business Group Assistance, Uninhabitable House Assistance, Cash Direct Assistance, Assistance for the Abandoned and Disabled Elderly, Access to Public Services, and Other Social Services. Good policies must be guarded so that the assistance can be channeled according to the target. The aspect of equitable distribution of aid is also important so that no one feels disadvantaged by the community in need. In the success of this effort, it is necessary to apply the Waterfall Model in the Development of Web-Based Social Assistance Applications to find out which communities need this assistance more and it can be channeled on target.